Estudo da captura de CO2 utilizando adsorventes modificados via simulação molecular - Lima, Adriano Erique de Oliveira (2012)
The high levels of CO2 emissions over the last century have generated concern and alert worldwide. Incentives to promote technologies for CO2 capture and storage are highlighted in this situation. Among the viable alternatives to capture that gas is the adsorption process. The literature contains many experimental studies of CO2 adsorption in various impregnated materials, despite that, few papers are devoted to the understanding of such phenomena at the atomic level. This study investigates the CO2 adsorption in X-faujasites and activated carbons impregnated with monoethanolamine (MEA) using molecular simulation. Thus, models of MEA, CO2, faujasite and activated carbon were proposed. For faujasite, the structure was modeled based on the crystallographic data reported in the literature. For activated carbon, the pores were represented by the slit pores model of graphene and the study was conducted in three pore sizes (8.9, 18.5, 30.9 Å) to represent different regions of the adsorption and also allow for data correlation with the commercial activated carbon WV-1050. The CO2 molecule was modeled in the three-centers (faujasites tests) and one-center (carbons tests) models. The adsorbents were loaded with increasing amounts of monoethanolamine and the impact of this addition was evaluated through a set of simulated CO2 isotherms using the Grand Canonical Monte Carlo (GCMC) method. With the model faujasite/MEA/CO2, it was possible to reproduce the decreasing experimental CO2 adsorption with increased MEA concentration. In carbons, it was observed that the values of adsorbed CO2 at high pressure (above 4 bar) always decrease with MEA increasing loadings for both pores, as verified experimentally in real carbons. However, the simulation has shown that the amount adsorbed at low pressures (below 1 bar) is enhanced with monoethanolamine concentration in carbonaceous material. These results, considering the techniques used in this study, indicate that the activated carbon and NaX systems modified with monoethanolamine are unfeasible for capturing CO2 if adsorption capacity is the only criterion to take into account